Specific features of abbreviations ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The article explores the specific features and characteristics of abbreviations. It discusses the various types of abbreviations, including acronyms, initialisms, and contractions, and explains how they are formed and used in written and spoken language. The article also delves into the rules and guidelines for creating and employing abbreviations effectively, as well as the potential challenges and ambiguities that can arise from their usage. Moreover, it may explore the role of abbreviations in different fields such as medicine, technology, and business, and how they contribute to efficient communication. Overall, the article provides a comprehensive overview of the specific features of abbreviations and their significance in modern language.